2012
DOI: 10.1177/1076029611431955
|View full text |Cite
|
Sign up to set email alerts
|

AssessMent of ProphylAxis for VenouS ThromboembolIsm in Hospitalized Patients

Abstract: Our thromboprophylaxis results were comparable to that of Western countries. Improved thromboprophylaxis appropriateness, which requires improving the physicians' thromboprophylaxis awareness and knowledge, could reduce the rate of in-hospital VTE and translate into better patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…Median and 25-75 percentile values resulted 9 (4-16), 3 (1-10), and 4 (1-9) days for phases 1, 2 and 3, respectively; b) the length of ICU stay progressively decreased (expressed as median and 25-75 percentile) from 14 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22), 7 (4-15.5) to 6 (4-12) days, with statistically significant difference between phases 1 and 2 or 3 (p b 0.0001 for both), but not between phase 2 vs phase 3; c) the ICU mortality rate did not change significantly throughout the 3 phases of the study; d) during the 3 phases no pulmonary embolism was clinically suspected or diagnosed in DVT positive patients ; during the second phase pulmonary embolism was reported at autopsy in one patient with known DVT, but it was not considered as the primary cause of death in that patient.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Median and 25-75 percentile values resulted 9 (4-16), 3 (1-10), and 4 (1-9) days for phases 1, 2 and 3, respectively; b) the length of ICU stay progressively decreased (expressed as median and 25-75 percentile) from 14 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22), 7 (4-15.5) to 6 (4-12) days, with statistically significant difference between phases 1 and 2 or 3 (p b 0.0001 for both), but not between phase 2 vs phase 3; c) the ICU mortality rate did not change significantly throughout the 3 phases of the study; d) during the 3 phases no pulmonary embolism was clinically suspected or diagnosed in DVT positive patients ; during the second phase pulmonary embolism was reported at autopsy in one patient with known DVT, but it was not considered as the primary cause of death in that patient.…”
Section: Resultsmentioning
confidence: 99%
“…In the study by Lecumberri et al the usefulness of electronic alert for the improvement of DVT prophylaxis prescription was maintained over two years [12]. In a review by Tooher et al, the authors state that the combination of multiple active strategies aimed at reminding clinicians to calculate individual DVT risk and at assisting the selection of appropriate prophylaxis, resulted in the achievement of optimal outcomes [9].On the contrary, the passive dissemination of guidelines has little effect on the improvement and maintenance of DVT prophylaxis prescription [17].…”
Section: Discussionmentioning
confidence: 95%
“…Effective DVT prophylaxis (mechanical and pharmacological) can reduce the morbidity and mortality of VTE among hospitalized patients [98], but studies examining thromboprophylaxis of patients who are obese are limited [99]. The American College of Chest Physicians (ACCP) guidelines do not recommend using mechanical prophylaxis alone for VTE prevention among patients with morbid obesity unless a high bleeding risk precludes the use of pharmacological prophylaxis; however, the ACCP guidelines do suggest weight-based dosing for certain anticoagulation medications for VTE prophylaxis [100].…”
Section: Prevention Of Vte Associated With Obesitymentioning
confidence: 99%
“…Several studies have demonstrated the necessity of adjusting the anticoagulant loading dose and dosing interval to achieve optimal anticoagulation among patients who are morbidly obese [99,101]. Suboptimal adherence to prophylaxis schemes or inappropriate prophylaxis (underprophylaxis of patients who are severely obese or overprophylaxis of patients who are of normal weight or who are underweight) has been reported [98,99,102]. Moreover, both the ACCP and the National Institute for Health and Clinical Excellence underscore the importance of individualized prophylaxis according to the estimated risk of VTE [103].…”
Section: Prevention Of Vte Associated With Obesitymentioning
confidence: 99%
“…1). 36,38 In brief, whereas for patients at low risk of VTE the state of prophylaxis reception is the only important parameter, for at-risk patients, along with prescription of some form of thromboprophylaxis, the correct choice, duration (i.e., when to start and when to stop), and dosing (if pharmacological) of prophylaxis would also be of significance.…”
Section: Contemporary Thromboprophylaxis Practice Around the World: Smentioning
confidence: 99%